Analisis Tingkat Kepuasan Konsumen terhadap Kualitas Produk dan Pelayanan Jaya Coffee Roasters menggunakan Metode Importance Performance Analysis dan Metode Customer Satisfaction Index - Wiratama, I Made Adi; Wiranatha, Agung Suryawan; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): Maret, 2022)
This study aims to analyze the level of consumer interest in the quality of products and services at Jaya Coffee Roasters, analyze the performance level of product and service quality, and analyze the level of consumer satisfaction with the quality of products and services at Jaya Coffee Roasters. The method used in this study is the IPA (methodImportance Performance Analysis) and Customer Satisfaction Index (CSI) by using 75 consumers. The results of the study using themethod Importance Performance Analysis and questionnaire data processing concluded that the product quality attributes that became the main priority agenda to improve their performance were the consistency of drinks for each serving while the service quality attributes that became the main priority agenda to improve their performance were the attributes of comfort, cleanliness, and neatness. place, Cleanliness and tidiness of employees and Accuracy in service and presentation. For the Customer satisfaction index (CSI) product quality was obtained at 69.05% and the Customer satisfaction index (CSI) obtained for service quality was 74.12%. These results indicate that consumers of Jaya Coffee Roasters satisfied. Keywords : Customer Satisfaction , Jaya Coffee Roasters, Importance Performance Analysis, Customer satisfaction index